2008
DOI: 10.1063/1.2839397
|View full text |Cite
|
Sign up to set email alerts
|

Infrared photocurrent response of charge-transfer exciton in polymer bulk heterojunction

Abstract: We study the charge-transfer exciton absorption and photocurrent response in solution-processed bulk heterojunction based on poly(3-hexylthiophene) donor and (6,6)-phenyl-C61-butyric acid methyl ester acceptor in the near-infrared wavelength region. While the exciton absorption exists only for wavelength below 650nm, direct generation of charge-transfer exciton formed between the donor and acceptor extends the absorption wavelength to 950nm. For films with micrometer thickness, the photon-to-electron conversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…OPDs utilizing thick junctions have previously been reported 15,22,33,35 . In particular, Armin et al 35 recently described photodiodes with impressive performance metrics for broadband visible, IR-blind light detection using the archetypal bulk heterojunction organic semiconductor donor: acceptor blend of PCDTBT:PC70BM [(poly[N-9 00 -heptadecanyl-2,7-carbazole-alt-5,5-(4 0 ,7 0 -di-2-thienyl-2 0 ,1 0 ,3 0 -benzothiadiazole)]: PC70BM].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…OPDs utilizing thick junctions have previously been reported 15,22,33,35 . In particular, Armin et al 35 recently described photodiodes with impressive performance metrics for broadband visible, IR-blind light detection using the archetypal bulk heterojunction organic semiconductor donor: acceptor blend of PCDTBT:PC70BM [(poly[N-9 00 -heptadecanyl-2,7-carbazole-alt-5,5-(4 0 ,7 0 -di-2-thienyl-2 0 ,1 0 ,3 0 -benzothiadiazole)]: PC70BM].…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that this is not a particularly efficient method to produce a NIR response since the CT state absorption is very weak in organic semiconductors 21 and therefore extremely thick junctions (410 mm) are required for light harvesting via CT states. As a consequence, the OPDs of Yang et al 22 could only be operated at extremely large reverse bias voltages (4100 V), and they also had a very high dark current noise. A truly narrowband (FWHMo100 nm), low noise, visible-blind NIR detector is yet to be realized.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 In general the photoresponse of photodetectors is determined by the absorption of the active layer. 11 The results showed that the photoresponse could be changed from visible to infrared by simply increasing the thickness of the active layer. Most conjugated polymers have the response in the visible range due to the fact that the band gap of most organic semiconductor is higher than 2 eV.…”
mentioning
confidence: 99%